Critical developments of 2017: a review of the literature from selected topics in transfusion. A committee report from the AABB Clinical Transfusion Medicine Committee. Issue 4 (9th March 2018) - Cushing, Melissa M.; Kelley, James; Klapper, Ellen; Friedman, David F.; Goel, Ruchika; Heddle, Nancy M.; Hopkins, Courtney K.; Karp, Julie Katz; Pagano, Monica B.; Perumbeti, Ajay; Ramsey, Glenn; Roback, John D.; et al.
Abstract : BACKGROUND: The AABB compiles an annual synopsis of the published literature covering important developments in the field of Transfusion Medicine. For the first time, an abridged version of this work is being made available in TRANSFUSION, with the full‐length report available as an Appendix S1 (available as supporting information in the online version of this paper). STUDY DESIGN AND METHODS: Papers published in 2016 and early 2017 are included, as well as earlier papers cited for background. Although this synopsis is comprehensive, it is not exhaustive, and some papers may have been excluded or missed. RESULTS: The following topics are covered: duration of red blood cell storage and clinical outcomes, blood donor characteristics and patient outcomes, reversal of bleeding in hemophilia and for patients on direct oral anticoagulants, transfusion approach to hemorrhagic shock, pathogen inactivation, pediatric transfusion medicine, therapeutic apheresis, and extracorporeal support. CONCLUSION: This synopsis may be a useful educational tool.